Prevalence of prediabetes in patients with metabolic risk - Matos, Lívia Nascimento de; Giorelli, Guilherme de Vieira; Saado, Amir; Dias, Cristiane Bitencourt (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Early diagnosis of prediabetes should be done to avoid complications relating to diabetes mellitus (DM). The aim here was to assess the prevalence of prediabetes among individuals at high risk of developing DM, and to seek variables relating to glucose intolerance (GI) among individuals with normal fasting plasma glucose (FPG). DESIGN AND SETTING: Cross-sectional study at Hospital do Servidor Público Estadual, São Paulo. METHODS: The FPG and glucose tolerance test (GTT) were analyzed, from which the subjects were divided as follows: group 1 (FPG and GTT both normal), group 2 (normal FPG but abnormal GTT), group 3 (abnormal FPG but normal GTT), and group 4 (FPG and GTT both abnormal). The subjects’ clinical, laboratory and anthropometric profile was determined. RESULTS: 138 subjects were studied: 44 in group 1, 11 in group 2, 33 in group 3 and 50 in group 4. The prevalence of prediabetes was 68.0%. Group 4 individuals were older than group 1 individuals [69.0 (55.5-74.0) versus 58.9 ± 11.8 years; P < 0.05], with greater prevalence of risk conditions for DM [5.0 (4.0-5.0) versus 4.0 (3.0-5.0); P < 0.05]. Among individuals with normal FPG, GI prevalence was 20.0%. No variables analyzed correlated with GTT. CONCLUSION: The prevalence of prediabetes was 68.0%, and 20.0% of subjects with normal FPG had GI. Although some anthropometric, clinical and laboratory variables have been correlated with DM and prediabetes, none, except for GTT, was able to screen for GI among subjects with normal FPG in the present study.